The progressive role of acoustic cavitation for non-invasive therapies, contrast imaging and blood-tumor permeability enhancement. (2nd October 2016) - Aw, Moom Sinn; Paniwnyk, Larysa; Losic, Dusan
ABSTRACT: Introduction : Drug delivery pertaining to acoustic cavitation generated from ultrasonic (US) irradiation is advantageous for devising smarter and more advanced therapeutics. The aim is to showcase microbubbles as drug carriers and robust theranostic for non-invasive therapies across diverse biomedical disciplines, highlighting recent technologies in this field for overcoming the blood-brain barrier (BBB) to treat cancers and neurological disorders. Areas covered : This article reviews work on the optimized tuning of ultrasonic parameters, sonoporation, transdermal and responsive drug delivery, acoustic cavitation in vasculature and oncology, contrast imaging for real-time magnification of cell-microbubble dynamics and biomolecular targeting. Scholarly literature was sought through database search on key terminology, latest topics, reputable experts and established journals over the last five years. Expert opinion : Cavitation offers immense promise in overcoming current diffusion and convection limitations for treating skull/brain/vascular/tissue injuries and ablating tumors to minimize chronic/acute effects. Since stable cavitation facilitates the restoration of US-opened BBB and the modulation of drug concentration, US equipment with programmable imaging modality and sensitivity are envisaged to create safer miniaturized devices for personalized care. Due to differing biomedical protocols with regard to specific medical conditions, quantitative and qualitative controls are mandatory before translation to real-life clinical applications can be accomplished.